Trauma KDRT dan Perilaku Posesif Remaja: Studi Kasus di Pusat Rehabilitasi Serang: Penelitian - Wiwin Sulistiyawati; Nadirah, Yahdinil Firda (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This qualitative case study aims to explore the impact of witnessing Domestic Violence (DV) and parental divorce on adolescent mental health, focusing on the case of F (30 years old), who was treated at the